PEMAKNAAN MIN AL-DHULUMAT ILA AL-NUR DALAM USAHA TRANSFORMATIF LEMBAGA PENDIDIKAN ISLAM - Muslim, Moh. (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2018)
The effort to develop an Islamic educational institution can not only be built on the concept of Aqliyah theory, but also based on the concept of God revelation. One of the explicit messages of God revelation is the phrase min adhulumatilaannur (from the darkness to the lightness). Implicitly, this phrase implies a transformation process from dhulumat (darkness) to an-nur (lightness). The process of transformation needs to be elaborated intact and holistic, how to interpret it; which will be formulated into the implementative formulation of the phrase.The phrase min al dhulumat ila an-nur conceptually there are three dimensional meaning that includes: 1). Textual, textual meaning of min al-dhulumatilaannur is from the darkness to the lightness, 2). Contextual, contextual meaning of min al-dhulumatilaannur; there are some interpretations from the interpreter whose essence is changing from disbelief to the faith, from apostasy to the faith, from ignorance to knowledge, and 3). Reconceptualization, there is a relevance of the concept min al-dhulumatilaannur with the management of education,that related to the transformation process that must be done to accept a change.Actualization of transformation can be done on some basic elements of education, i.e., students, teachers, headmasters/ managers, supervisors, employees and parents.